1995
DOI: 10.1002/hep.1840210615
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of hepatobiliary and renal elimination of cysteinyl leukotrienes by positron emission tomography

Abstract: N-Acetyl-leukotriene E4 has been identified as an endogenous, biologically less active cysteinyl leukotriene metabolite in rodents and humans. To evaluate the ratio of hepatobiliary to renal elimination of leukotrienes noninvasively by positron emission tomography (PET), we synthesized N-[11C]acetyl-leukotriene E4 by chemical N-acetylation of leukotriene E4. After the intravenous injection of N-[11C]acetyl-leukotriene E4 in normal rats and monkey, uptake by the liver and subsequent excretion into bile were lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…Additionally, hepatotoxicants that are handled by the liver in a manner similar to MEB may cause significant toxicity in patients with obstructive cholestasis, where biliary excretion is impaired and a compensatory increase in hepatic egress occurs. Simulations of obstructive cholestasis revealed that liver exposure was increased 60% compared to normal subjects; these results are in accordance with changes in transit time through the liver that Guhlmann et al (19) observed for N-acetyl LTE 4 in rats with cholestasis due to bile duct obstruction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, hepatotoxicants that are handled by the liver in a manner similar to MEB may cause significant toxicity in patients with obstructive cholestasis, where biliary excretion is impaired and a compensatory increase in hepatic egress occurs. Simulations of obstructive cholestasis revealed that liver exposure was increased 60% compared to normal subjects; these results are in accordance with changes in transit time through the liver that Guhlmann et al (19) observed for N-acetyl LTE 4 in rats with cholestasis due to bile duct obstruction.…”
Section: Discussionsupporting
confidence: 89%
“…The TR − rat strain has a hereditary mutation in the Abcc2 gene; like DubinJohnson patients, TR − rats exhibit impaired bilirubin excretion (due to the absence of canalicular Mrp2) and enhanced basolateral expression of Mrp3 (17,18). Consistent with these alterations in TR − rats, deficient biliary excretion of N-acetyl-leukotriene E 4 , an Mrp2 substrate, was compensated by leukotriene urinary excretion; interestingly, mean liver transit time was increased more than 3-fold in TR − compared to normal Wistar rats (19).…”
Section: Introductionsupporting
confidence: 60%
“…21 This pioneering PET study showed how, in the case of impaired hepatic functionality (due to hereditary transporter deficiencies or bile duct obstruction), the extraction of leukotriene metabolites can be switched from hepatobiliary to renal clearance.…”
Section: [ 11 C]-cholylsarcosine As a Pet Tracer To Study Bile Acid Tmentioning
confidence: 99%
“…Also, drug metabolites 17,19 and endogenous compound derivatives 20,21 have been successfully labeled with 11 C and employed as PET tracers. Table 1 lists the PET tracers that have been used to study hepatic transporters.…”
Section: Pet Tracers To Study Hepatic Transportersmentioning
confidence: 99%
See 1 more Smart Citation